Effects of post-mineralization metamorphism and deformation on Ni-Fe sulfides and their remobilization in the Pulju Greenstone Belt, Northern Finland - Díaz Carreño, Juan Camilo (Helsingin yliopisto, 2024)
The Pulju Greenstone Belt (PGB), located on the northwesternmost edge of the Central Lapland Greenstone Belt (CLGB) in Finland, bears significant potential for Ni-sulfide deposits. The Paleoproterozoic differentiated komatiites of the Mertavaara Formation host the Hotinvaara Ni-prospect which is the most economically promising mineralization to date within the PGB. Following the completion of ~ 15.52 km addition diamond core drilling, Nordic Nickel Ltd. completed the Mineral Resource Estimate (MRE) for the Hotinvaara Ni-prospect, indicating 418Mt at 0.21% Ni, 0.01% Co, and 53ppm Cu for 862,800t of contained Ni, 40,000t of contained Co and 22,100t of contained Cu. The Hotinvaara mineralization occurs in strongly metamorphosed MgO-rich olivine cumulates as moderately- to weakly-interconnected sulfide disseminations and as larger pentlandite-pyrrhotite blebs. In addition, Ni-sulfides occur locally as massive 10’s of cm to m-scale, sulfide veins containing up to 9.61% Ni, 0.17% Cu, and 0.36% Co. Mineralized offsets are also found within the metasedimentary rocks of the Sietkuoja Formation and mafic to intermediate tuffites of the Vittaselkä Formations; however, these occurrences are mainly pyrrhotite-dominant and do not have economic interest. Chalcopyrite, pyrite, mackinawite, cobaltite-gersdorffite, violarite, and valleriite are present in subordinate amounts (<5%). All mineralization types have been subject to multistage deformation events (D1-D4) at lower-amphibolite facies metamorphic conditions, which led to the development of deformation textures, recrystallization, and annealing of sulfides as well as paragenetic relationships indicating remobilization of sulfides. On average, the sulfide phase contains 12.63 wt.% Ni and 0.59 wt.% Co, 0.54 wt.% Cu, and very low PGE abundances, implying that the sulfide fraction of the Hotinvaara Ni-prospect is Ni-(Co)-enriched and Cu-PGE-depleted. Nickel contents of the sulfide phases are extremely variable (1–36 wt.%) at Hotinvaara, even between closely spaced samples, ...